Pengabdian Kepada Masyarakat "Profesi Akuntan di Era Kekinian" - Wicaksono, M. Resa (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The Industrial Revolution 5.0 requires the accounting profession to adapt to the development of information technology, while many students still lack understanding of the accounting profession in the modern era. The purpose of this seminar is to provide an overview of accounting professions in the current era and the necessary preparations. The method used was a seminar with a descriptive qualitative approach through panel discussions and Q&A sessions conducted by PPAk students of Jenderal Soedirman University, which included discussions on accounting professions such as forensic accountants, digital accountants, and tax technology specialists, as well as the challenges faced by accountants in the modern era. The seminar was attended by 56 participants consisting of students from Muhammadiyah University Prof. Dr. Hamka and the public. The results showed that the accounting profession in the modern era is not only focused on preparing financial reports but also on the use of information technology such as software, artificial intelligence (AI), and other related tools. The seminar concluded that the preparation of prospective professional accountants requires not only mastery of accounting theory but also skills in information technology, data analysis, and a broad understanding of the various accounting professions.